The Effects of Junk Food Consumption on Incidence of Early Puberty in Adolescent Females - Kustin Kustin; Farida Wahyuningtyias; Al Munawir (Health Notions, 2017)
The transition between childhood and adulthood is the period of puberty be marked is rapid body growth, the appearance of secondary sex features, menarche, and psychic changes. Menarche is too early to be associated with risk factors for some malignant disease such as ovarian cancer, breast cancer, and myoma. Hyperplasia cholecystitis, incidence of uterine cancer and risk of Non Insulin Dependent Diabetes Mellitus (NIDDM / Type II) as adults. The consumption of junk food tends to increase from year to year. Consumption of junk food tends to increase which affects nutritional improvement. This is because the fat content, animal protein and trans fat contained in junk food will trigger the release of hormones that affect the occurrence of menarche and the emergence of secondary signs in children faster than normal age. The purpose of this study analyzed the effect of junk food consumption on early puberty incidence on female teenagers of junior high school in Jember regency. This study was conducted in two stages, the first quantitative observational analytic study with cross sectional design and the second stage of the laboratory using pre experimental design with one shot case study approach for the most frequently consumed food samples. The sample of this research is 88 female teenagers of junior high school. Data analysis was processed using logistic regression test of significance level p<0.05. Result showed that there was significant effect between junk food consumption pattern on early puberty statistically p = 0.002. The laboratory test results also showed that the fat content of junk food on average over 20%. Consumption habits, consumption time and percentage of fat consumed from junk food affect the incidence of early puberty in female teenagers, while the frequency of consumption does not affect the incidence of early puberty. Keywords: Early puberty, Junk food, Fat